Progress and obstacles in transplantation of brown adipose tissue or engineered cells with thermogenic potential for metabolic benefits - Zhu, Tao; Chen, Xu; Jiang, Shenglu (Frontiers in Endocrinology, 2023)
Transplantation of brown adipose tissue(BAT) or engineered thermogenic progenitor cells or adipocytes has received much attention for the improvement of obesity and metabolic disorders. However, even though the thermogenic and metabolic potential exists early after transplantation, the whitening of brown fat graft occurs with the metabolic function significantly impaired. In this review, specific experiment designs, graft outcomes and metabolic benefits for the transplantation of BAT or engineered cells will be discussed. The current advancements will offer guidance to further investigation and the obstacles appeared in previous studies will require innovation of BAT transplantation methods.